Sosialisasi Mitigasi Bencana Gempa Bumi di SMP Negeri 8 Ambon Negeri Hutumuri - Ronald D. Hukubun; Eva S. Ratuluhain; Frijona F. Lokollo; Degen E. Kalay; Valentine D. Saleky; Intan Buton; Ivanual M. Wairata (Jurnal Nusantara Berbakti, 2023)
Maluku is part of the Indonesian territory which is traversed by the meeting point of 3 active tectonic plates, namely the Indo-Australian plate (southern part), the Eurasian plate (Western and North parts) and the Pacific plate (Eastern part). This causes the tectonic activity in Maluku and the islands therein to be quite high, and it is very prone to earthquakes and even tsunamis. Earthquake events cannot be predicted both when and how large the intensity of the earthquake will occur, so it is necessary to carry out early debriefing regarding earthquake disaster mitigation. This activity was carried out at SMP Negeri 8 Ambon Negeri Hutumuri, South Leitimur District, Ambon City, which is one of the coastal schools in Maluku. The material presented included an introduction to Indonesia's tectonic order, definitions of disaster mitigation, actions to be taken before, during and after an earthquake. Based on the results of the socialization, it appears that the students were very enthusiastic and had quite good knowledge regarding how mitigation and evacuation should be carried out.